Artificial Intelligence in Medicine: Transforming Diagnosis, Treatment, and Healthcare Delivery (Journal of Medical & Health Sciences Review, 2023)
This article explores the rapidly evolving field of artificial intelligence (AI) in medicine, focusing on its impact on diagnosis, treatment, and healthcare delivery. Machine learning algorithms are transforming medical practices by analyzing vast datasets, leading to earlier disease detection, personalized treatment plans, and improved resource allocation. However, ethical considerations regarding data privacy, bias, and transparency remain. Understanding AI's potential and limitations is crucial for navigating its ethical implementation and maximizing its benefits for patients and healthcare systems.Keywords: Artificial intelligence, machine learning, healthcare, diagnosis, treatment, precision medicine, ethics, bias, transparency.